Pengembangan UMKM melalui Optimalisasi Digital Marketing di Dusun Sawahan, Trimurti, Srandakan - Hatta, Muhammad; Hartono, Renata Julianty; Adzani, Muhammad Etandra Fara; Putri, Syahmilian; Swayani, Sevila Genna; Apriliyan, Vicky; Saraswati, Dian; Ariswara, Resti Lintang; Latif, Firsa Ghulam; Reyhan, Ahnaf; Muallidin, Isnaini (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This community service program aims to enhance the capacity and digital marketing skills of Micro, Small, and Medium Enterprises (MSMEs) in Dusun Sawahan, Trimurti Village, Srandakan District, Bantul Regency through the optimization of social media, particularly Instagram. The method used is Participatory Action Research (PAR), which consists of four stages: socialization, training, mentoring, and evaluation. The training was divided into two sessions: the first session introduced Instagram, while the second session covered the fundamentals of digital marketing and product photography techniques. Evaluation was conducted using pre-tests and post-tests to measure participants' understanding. The results showed that 95% of participants comprehended the basic concepts of digital marketing in the first session; however, this percentage decreased to 75% in the second session due to a reduction in participant attendance caused by time constraints. Of the 20 participants who received mentoring, 17 actively promoted their businesses on Instagram, while the remaining 3 chose not to participate. The main challenges encountered included limited technical skills, time constraints, and age-related factors. Therefore, intensive mentoring and further training on Instagram Reels content creation are necessary to maximize its utilization in digital marketing